Association of Plasma Folate, Vitamin B12, and Betaine With Total Homocysteine in Pregnancy, and Effect Modification Due to Folic Acid Versus Natural Folate Supplementation. (14th June 2022) - Cochrane, Kelsey; Devlin, Angela; Elango, Rajavel; Hutcheon, Jennifer; Karakochuk, Crystal
Abstract: Objectives: Elevated circulating total homocysteine (tHcy) is associated with numerous pregnancy complications. Determinants of circulating tHcy include folate, vitamin B12, and betaine status, which catalyze the remethylation of homocysteine to methionine. In countries with folic acid food fortification, vitamin B12 and betaine are reported as stronger predictors of tHcy than folate. We evaluated the association between plasma folate, vitamin B12, and betaine with plasma tHcy in pregnancy, and any effect modification due to supplementation with folic acid versus 5-methyltetrahydrofolate (natural folate; 5-MTHF). Methods: Pregnant women (n = 60) in Vancouver, BC, were randomized to 0.6 mg folic acid or 5-MTHF for 16 weeks, starting at 8–21 weeks gestation. Dietary folate intake was recorded at baseline. A 3-hour fasting blood sample was collected at baseline and endline for quantification of plasma folate (LC-MSMS), vitamin B12 (immunoanalyzer), betaine and tHcy (HPLC-MSMS). Linear regression was used to assess the association of endline plasma folate, vitamin B12, and betaine with endline tHcy, with folate group as an interaction term, adjusting for baseline tHcy, weeks gestation, and dietary folate intake. As the trial is not yet unblinded, groups are presented as "A" and "B". Results: The median [IQR] concentrations of plasma analytes at endline in groups "A" and "B" were: folate 58 [54, 65] and 66 [61, 82] nmol/L; vitamin B12 204 [159, 239] and 206 [166, 300] pmol/L; betaine 15 [13, 16] and 14 [12, 17] µmol/L; tHcy 4.9 [4.5, 5.6] and 5.2 [4.7, 5.8] µmol/L, respectively. Folate group did not significantly modify the association of tHcy with folate (p = 0.39), vitamin B12 ( p = 0.42), or betaine (p = 0.56). Overall, there was no association (β, 95% CI) of endline plasma folate, vitamin B12, or betaine with the outcome tHcy (µmol/L): folate −0.002 (−0.01 to 0.009); tB12 −0.0005 (−0.002 to 0.0005); betaine 0.02 (−0.04 to 0.07). Baseline tHcy was the most significant predictor of endline tHcy in each model (β = 0.8, 95% CI 0.6 to 1.0). Conclusions: Folate, vitamin B12, and betaine concentrations were not associated with tHcy, nor was the effect modified by supplementation with folic acid versus 5-MTHF. In this group of n = 60 healthy pregnant women, baseline tHcy was the most important predictor of tHcy in later pregnancy. Funding Sources: Healthy Starts Catalyst Grant (BCCHR).